Development of collaboration, cooperation and innovation in the classroom based on projects (Docentes 2.0 Journal, 2021)
Project-based learning (PBL) is a fundamental tool to motivate students, allowing them to get involved in meaningful learning by feeling like the true protagonists. This research aimed to promote collaborative, cooperative, and innovative work to design, develop, and implement a prototype that allows managing a robotic arm (automaton) using an Arduino microcontroller. The presented problem to be solved was to a group of 16 students of the 3rd grade of Mechatronics Engineering, UTSC. They used six servo motors, three aluminum U-shaped structures, a clamp-shaped tool, an Arduino Uno board, a power source, a USB interface, a computer, a wooden base where they will hold components. They managed to structure a robot arm with 6 degrees of freedom capable of executing the microcontroller's movements. The observed development of the notable project improvement in their ability to work as a team and motivation develops the project. As critical thinking and propose solutions to the problems faced. The use of educational robotics in the classroom through the development of projects is a very efficient tool that leads students to develop skills, promote critical thinking, take the different concepts or theoretical approaches seen in class to a fundamental level of action.
Keywords: Inovation; Implementation; Proyects